Fast fashion: Consumptive behavior in fashion industry Generation Z in Yogyakarta - Widari, Tika; Aliffiati, Aliffiati; Indra, Muhammad (Yayasan Irwan Abdullah Cendekia, 2023)
The fashion emergence is a trend that is closely related to generation Z. The easy access to social media is one of the most effective diffusion modes of fashion trends. In addition, there are marketing techniques used by business actors to spread products by involving figures that are loved by generation Z, such as politicians, celebrities, artists, and other public figures. These figures involvement is able to attract the followers to follow the trend. The reason is that following trends can show one’s identity and increase self-confidence, it cannot be avoided by looking at the ways of fashion fans in Generation Z. Fashion trends that continue to roll quickly make them have consumptive behavior. This behavior must be taken seriously considering the waste impact generated from production can be a big problem for the environment